Benign and Malicious Envy Scale: Cross-cultural Adaptation and Validity Evidence for Adolescents - Peixoto, Evandro Morais (2021)
Although there are few Brazilian studies on this subject, envy is a universal phenomenon present in the cultural and social spheres. This research aimed to conduct a cross-cultural adaptation to Brazilian Portuguese and to evaluate validity evidence for Benign and Malicious Envy Scale (BeMas), a measure of benign and malicious envy. A total of 248 adolescents, aged 12 to 17 years old (M=13.93 ±1.39, 47.9% of boys) participated in this research. Evidence of validity based on content, internal structure, relationship to other variables (stress, anxiety, depression, global distress, and life satisfaction) and reliability indicators were estimated. The exploratory factor analysis suggested the adequacy of the internal structure composed by two factors, demonstrating the equivalence of the internal structure with the original version, as well as good indicators of reliability (ω= 0.760 e 0.823) and relationships with external variables consistent with the theoretical hypotheses. The Results suggest adequacy of the instrument.